Pengembangan Kualitas Produk Dalam Upaya Meningkatkan Volume Penjualan Produk Home Industry Madu Lebah Kelulut “Nano Alami” - Chandra, Rinaldi Aria; Irwansyah, Irwansyah (Universitas Lambung Mangkurat, 2023)
Product quality is seen as being able to influence product purchasing decisions by prospective consumers so as to increase the sales volume of a product. Previously, the